Efficacy of Intra-arterial Norcantharidin in Suppressing Tumour 14C-labelled Glucose Oxidative Metabolism in rat Morris Hepatoma. Issue 2 (1996) - Mack, Peter; Ha, Xiao-Fang; Cheng, Li-Yao
Abstract : Norcantharidin is the demethylated form of Cantharidin, which is the active ingredient of the blister beetle, Mylabris, a long used Chinese traditional medicine. Though not well publicised outside China, Norcantharidin is known to possess significant anti-hepatoma activity, and is relatively free from side effects. In the present study, glucose oxidation in tumour and liver tissue slices harvested from hepatomabearing animals was quantified by measuring the radioactivity of 14 C-labelled CO released from 14 C-glucose in oxygen-enriched incubation medium. Results were expressed asa tumour/liver ratio. For comparison, treatments with Norcantharidin, Adriamycin and with hepatic artery ligation were studied. The mean tumour/liver ratio was 4.2+2.2 in untreated controls, but dropped significantly to 2.3+0.5 (p<0.05) with intra-arterial Norcantharidin (0.5 mg/kg) and to 2.3+0.7 (p<0.05) with intra-arterial Adriamycin (2.4 mg/kg), and to 2.2+0.7 (p<0.05) with hepatic artery ligation. However, with intravenous Adriamycin at 2.4 mg/kg, the mean tumour/liver ratio was reduced to only 3.5+2.0 and was not significantly different from untreated controls. It is concluded that intra-arterial Norcantharidin is as effective as intraarterial Adriamycin and hepatic artery ligation in suppressing tumour glucose oxidative metabolism. These results imply that Norcantharidin may have a role to play in the chemotherapy ofprimary livercancer.